6) a = -2, b = 5, c = -4, and d = 6; 2a^2+3b^2
2a^2 + 3b^2 = 2(-2)^2 + 3(5)^2 = 2(4) + 3(25) = 8 + 75 = 83.
7) a = -2, b = 5, c = -4, and d = 6; 2(a+b)
2(a + b) = 2(-2 + 5) = 2(3) = 6.
8) a = -2, b = 5, c = -4, and d = 6; 4(2a - d)
4(2a - d) = 4(2(-2) - 6) = 4(-4 - 6) = 4(-10) = -40.
9) a = -2, b = 5, c = -4, and d = 6; a(b + 3c)
a(b + 3c) = -2(5 + 3(-4)) = -2(5 - 12) = 2(12 - 5) = 2(7) = 14.
Note the 3rd step: -2(5 - 12) = 2(12 - 5): −(a−b)=b−a
10) a = -2, b = 5, c = -4, and d = 6; (8b) / (5c)
(8b) / (5c) = (8/5)(b/c) = (8/5)(-5/4) = -2.